2019
DOI: 10.1017/s0021859619000728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alternative feed additives and flint maize grain particle size on growth performance, carcass traits and nutrient digestibility of finishing beef cattle

Abstract: The current study evaluated growth performance and digestion responses of finishing bulls fed diets containing 825 g/kg flint maize [dry matter (DM) basis] ground to medium (1.66 mm; MG) or coarse particle sizes (2.12 mm; CG), with added monensin (26 mg/kg; DM basis; MON) or a blend of essential oils (BEO) + exogenous α-amylase (AM; 90 mg/kg + 560 mg/kg commercial product, respectively, DM basis). In Expt 1, 256 Nellore bulls were blocked by initial body weight (BW) (360 ± 11.7 kg) and assigned to 48 pens in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 62 publications
5
12
0
Order By: Relevance
“…Consistent with Gouvêa et al [ 44 ], the combination EO + ENZ did not affect apparent total tract digestion of OM, starch or NDF. Lack of treatment effects on total tract starch digestion is not surprising, in as much as apparent total tract starch digestion approached 100% for all treatments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with Gouvêa et al [ 44 ], the combination EO + ENZ did not affect apparent total tract digestion of OM, starch or NDF. Lack of treatment effects on total tract starch digestion is not surprising, in as much as apparent total tract starch digestion approached 100% for all treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Lack of treatment effects on carcass traits and tissue composition is consistent with previous comparisons of supplemental EO [ 8 , 43 ], EO + ENZ combination [ 44 ], and VM [ 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…Gouvêa et al [ 13 ] and Meschiatti et al [ 14 ] reported an increase in feed intake (7.4 and 8.6%, respectively) when MON was replaced by EOA. However, according to Gouvêa et al [ 13 ], the roughage source may affect the DM intake when EOA is provided.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary inclusion of ionophores and non-ionophores as sole feed additives or in combination has increased propionic acid production, improved feed efficiency, and reduced the incidence of metabolic disorders compared to diets containing no additives [ 11 , 12 ]. However, plant compounds with antibacterial properties and exogenous enzymes have been increasingly used to replace antibiotics in feedlot diets [ 13 , 14 ]. In this context, studies [ 13 , 14 ] have shown that animals fed diets containing essential oils plus exogenous α-amylase (EOA) may show increased feed intake, starch digestibility, and average daily gain compared to those fed diets with other feed additives, such as MON.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation